Fertility Choice and Financial Development - Valerio Filoso; Erasmo Papagni (Economics and Econometrics Research Institute (EERI), 2011)
We study the consequences of broader access to credit and to capital markets on household's decisions over the number of children. In a life-cycle model of choice with forward and backward caring between parents and children, we analyze the effects of relaxing adults' borrowing constrains and broadening the opportunities for financial investment, and show how the sign of these effects depends on the role of children as a normal or inferior good in parents' preferences. We estimate the quantitative implications of our theoretical model on data from 145 countries over the period 1980-2006. Empirical results indicate that improved access to credit reduces fertility in poor countries and increases fertility in high-income countries. The effect of the development of capital markets on the number of children is negative in low-income countries and positive in the rich. When the analysis includes public pensions the main results remain the same. We also estimate the effect of the real interest rate, which proves significant and negative.
Keywords: D1; J13; G1; 330; Fertility; Financial Markets Development; Old-Age Security